Exploration culturable bacterial symbionts of sponges from Ternate Islands, Indonesia - AGUS TRIANTO; OCKY KARNA RADJASA; AGUS SABDONO; SAKTI IMAM MUCHLISSIN; RACHMAT AFRIYANTO; SULISTIOWATI SULISTIOWATI; SEPTHY KUSUMA RADJASA; PHILLIP CREWS; ERIN MCCAULEY (Society for Indonesian Biodiversity, 2019)
Abstract. Trianto A, Radjasa OK, Sabdono A, Muchlissin SI, Afriyanto R, Sulistiowati, Radjasa SK, Crews P, Mccauley E. 2019. Exploration culturable bacterial symbionts of sponges from Ternate Islands, Indonesia. Biodiversitas 20: 776-782. Multidrug resistance, (MDR) bacteria seriously threaten human health which causes a more difficult and extends the treatment period, and increases the risk of death. Sponges-associated bacteria, a well known for their rich in chemical classes and bioactivities, are the prolific producers of bioactive compounds. In order to search new sources of antibacterial compounds, we collected a total of 55 sponges from Ternate Island that provided 324 bacterial isolates. The data showed that sponges-isolates ratio in the anthropogenic area was relatively higher than the other collection sites. The isolates were screened for the antibacterial activity against Klebsiella pneumoniae-RSDK, K. pneumoniae-UI, Pseudomonas aeruginosa A-UI, P. aeruginosa B-UI, Staphylococcus aureus-UI, MRSA-UI, MRPA-UI, Bacillus subtilis-RSDK, B. subtilis-UI, Salmonella typhi-UI, and MDR E. coli. The isolates were able to inhibit 0-7 the pathogenic bacteria on 24 h and 48 h. The most active bacteria were identified as B. clausii, V. chiguensis, B. tropicus, P. marcusii, B. tropicus, V. parahaemolyticus, B. paramycoides, and V. dokdonensis. In conclusion, the sponges in the anthropogenic affected area have higher bacterial symbionts than that of in the pristine area. In this study, the results of isolation of the symbiont bacteria from sponge samples were obtained and morphologically observed for these bacterial isolates. The number of bacteria that were isolated were 133 bacterial isolates and ten isolates including producing active secondary metabolites